Playing-related Musculoskeletal Problems in Children Learning Instrumental Music: The Association Between Problem Location and Gender, Age, and Music Exposure Factors - Ranelli, Sonia; Straker, Leon; Smith, Anne (Science and Medicine, 2011)
Purpose: Playing-related musculoskeletal problems (PRMP) are common in adult musicians, and risk factors include gender, music exposure, and particularly instrument type. Emerging evidence suggests PRMP are common in children and adolescents and that risk factors may be similar. The aim of this study was to determine the prevalence of PRMP, both symptoms and disorders, and PRMP location in children and adolescents as well as the associations with gender, age, and music exposure factors such as type and number of instruments and playing time. Methods: This study surveyed 731 children (460 females), aged 7 to 17 years, studying instrumental music in government schools in Perth, Australia. Lifetime and monthly symptoms, monthly disorders (inability to play an instrument as usual), and PRMP location were examined. Chi-squared analyses were used to evaluate associations between gender, age, music exposure, and PRMP outcomes. Logistic regression evaluated the independent association of these potential risk factors with PRMP prevalence and location.Results: Sixty-seven percent of students reported PRMP symptoms at some point, 56% reported them within the last month, and 30% reported an inability to play as usual within the last month. After adjustment for gender and age, the type of instrument played (upper and lower strings, woodwind, and brass) was significantly associated with all PRMP (p<0.005) and playing three instruments was protective against monthly symptoms (OR 0.43, p=0.05). The right (24%) and left (23%) hand/elbow and neck (16%) were the most commonly reported PRMP locations, with females affected significantly more than males Prevalence of PRMP increased with age for neck (p<0.001), mid-back (p=0.007), low back (p<0.001), right hand/elbow (p=0.008), and mouth (p=0.011). PRMP prevalence for the left hand/elbow and right and left shoulders demonstrated high rates across all childhood ages. Odds ratios for the risk of PRMP in different locations varied by instrument played. Conclusions: The high prevalence and location of PRMP are important issues for child and adolescent instrumentalists. Gender, age, and music exposure are associated with PRMP risk and need to be addressed to ensure musicians' personal well-being and musical longevity.